Clonality, founder mutations, and field cancerization in human ulcerative colitis-associated neoplasia. - Leedham, S; Graham, T; Oukrif, D; McDonald, SA; Rodriguez-Justo, M; Harrison, R; Shepherd, N; Novelli, MR; Jankowski, J; Wright, N (2009)
BACKGROUND and AIMS: The clonality of colitis-associated neoplasia has not been fully determined. One previous report showed polyclonal origins with subsequent monoclonal outgrowth. We aimed to assess the clonality and mutation burden of individual crypts in colitis-associated neoplasias to try to identify gatekeeping founder mutations, and explore the clonality of synchronous lesions to look for field effects. METHODS: Individual crypts (range, 8-21 crypts) were microdissected from across 17 lesions from 10 patients. Individual crypt adenomatous polyposis coli (APC), p53, K-RAS, and 17p loss of heterozygosity mutation burden was established using polymerase chain reaction and sequencing analysis. Serial sections underwent immunostaining for p53, beta-catenin, and image cytometry to detect aneuploidy. RESULTS: In most lesions an oncogenic mutation could be identified in all crypts across the lesion showing monoclonality. This founder mutation was a p53 lesion in the majority of neoplasms but 4 tumors had an initiating K-RAS mutation. Some nondysplastic crypts surrounding areas of dysplasia were found to contain clonal p53 mutations and in one case 3 clonal tumors arose from a patch of nondysplastic crypts containing a K-RAS mutation. CONCLUSIONS: This study used mutation burden analysis of individual crypts across colitis-associated neoplasms to show lesion monoclonality. This study confirmed p53 mutation as initiating mutation in the majority of lesions, but also identified K-RAS activation as an alternative gatekeeping mutation. Local and segmental field cancerization was found by showing pro-oncogenic mutations in nondysplastic crypts surrounding neoplasms, although field changes are unlikely to involve the entire colon because widely separated tumors were genetically distinct.